PERANCANGAN SISTEM INFORMASI TOKO VARIASI MOTOR HYPERSPEED SEMARANG BERBASIS WEB (Information Technology and Telematics, 2016)
Abstract-  Technological  developments  are  now growing very rapidly and affects many aspects of life of human civilization.  Technology  was  created  as  a  tool  in  the  face  of human and ease in completing a job. Store information system design variations Hyperspeed motors utilize rapid information technology,  the  rapid  distribution  of  information  and  services quickly  to  market  products  obtained  by  the  consumer  via  the internet.  Store  information  system  design  variations Hyperspeed web-based motorcycle, which was built through the use Dreamweave, PHP and MySQL. In the design of this system consumers  can  book  through  the  web  of  existing  variation  in gadjet  or  mobile  phone  owned.  But  it  requires  an  internet connection.  After  penggujian  system  is  known  to  all  the functions  contained  in  the  system  of  managing  the  store reservation  data  Hyperspeed  variation  so  that  all  views  filtur supplied have been able to facilitate on the part of consumers looking for information or pengelolah systemKeywords:  System  Information  Design,  Dreamwever,    PHP and MySQL